تعليم العربية لأغراض سياحية في ماليزيا : تحليل الحاجات وتصميم وحدات دراسية - Zalika binti Adam (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2013)
The aim of this study is to investigate the needs for Arabic language for the purpose of tourism and lesson content design. Two hundred and ninety-two questionnaires were distributed and 59 interviews were conducted with 29 Malaysian and 30 Arab tourists. The questionnaire was used to find out the needs for the four main skills of Arabic proficiency specially in language course aimed at tourism. The respondents were also asked to suggest the vocabulary relevant to the needs of tourism. The results of the analysis on the Arabic language needs for the purpose of tourism can be used to design lessons. Student-centered learning processes through- problem solving, critical thinking, and self-learning were suggested. In addition, for lesson content design, the researcher used methods from Hutchinson and Water (1987), Ahmed Rushdi To'eima (2003) and Toba (1962), which touched on objectives, content, teaching methodology and evaluation. The researcher concludes that tourism requires teaching and learning needs in its contents. The findings of this research show the following: First, speaking skill is crucial for accurate information. Second, accents such the Saudi Arabian or Egyptian, have been recommended by most participants. Third, tourism encompasses development in economic and eco-tourism, politics, culture, education, and geography. These have sub-elements which can be used for lesson content design. Therefore, the researcher recommends that Arabic language be used in tourism sector in Malaysia.